Potential and Threat Analysis Towards Cybersecurity in South East Asia - Salsabila, Anna S; Fikri, Muflih D; Andika, Muhammad S; Harahap, Nanda A (Universitas Sebelas Maret, 2020)
Cybersecurity is a very strategic issue in maintaining a state’s stability, particularly in this modern era. The threats that can attack a state can no longer be physical or traditional threats but also cyber threat. In dealing with cases occurring related to the issue, Singapore initiated the establishment of ASEAN-Singapore Cybersecurity Centre of Excellence (ASCCE) to ascertain cybersecurity stability in ASEAN region. However, it of course results in various speculations and potencies likely occurring when cybersecurity is concentrated and controlled on one country only. Therefore, this journal analyzed ASCCE-related potency and threat likely occurring in ASEAN using Speech Act, Securitization, Wideners, International Cooperation, and Information Technology Management theories. In addition, the author also discussed the effectiveness of ASCCE performance in coping with cybercrimes and cyberthreats in ASEAN and their effect on ASEAN states.